Investigating proactive aggression in patients with borderline personality disorder and major depressive disorder using a modified version of the Taylor aggression paradigm - Boccadoro, Sara; Hüpen, Philippa; Raine, Adrian; Habel, Ute; Wagels, Lisa (Frontiers in Psychology, 2024)
Inappropriate reactive (provoked) aggression is common in various psychiatric disorders, including Borderline Personality Disorder (BPD) and, to a lesser extent, Major Depressive Disorder (MDD). Less is known about proactive (unprovoked) aggression in these patients, with mixed findings in the literature. Drawing from the current evidence, we expect higher trait aggression in both patient groups and higher behavioral proactive aggression and physiological arousal in patients with BPD compared to both MDD and healthy participants (HC). We investigated behavioral and psychophysiological correlates of proactive aggression in 23 patients with MDD, 20 with BPD, and 21 HC using a proactive version of the Taylor Aggression Paradigm (pTAP). The pTAP consists of reaction time games in which only the participant can interfere with the ostensible opponent's performance by modifying the blurriness of the opponent's screen. The levels of blurriness chosen by participants reflect their proactive aggression. We collected self-report measures of aggression and other personality traits. We further adopted a transdiagnostic approach by clustering participants based on proactive aggression characteristics. Both patient groups reported higher trait aggression than HC but not higher aggression in the task nor differences in the associated physiological arousal. Trial-by-trial mixed model analyses revealed that the group characterized by higher proactive aggression traits behaved more aggressively after losing, suggesting a role of frustration or sensitivity to loss. Our study confirms that patients with MDD and BPD report higher aggression than HC despite the absence of observable behavioral and psychophysiological differences and highlights the ubiquity of proactive aggression characteristics across diagnoses.